A pawn in someone else's game?: The cognitive, motivational, and paradigmatic barriers to women's excelling in negotiation. (2015) - Kennedy, Jessica A.; Kray, Laura J.
Abstract: Women's relatively worse performance in negotiation is often cited as an explanation for gender differences in advancement and pay within organizations. We review key findings from the past twenty years of research on gender differences in negotiation. Women do underperform relative to men in negotiation, but only under limited circumstances, which means the performance gap is unlikely due to lesser skills on their part. The barriers between women and negotiation excellence are of three types: cognitive, motivational, and paradigmatic. Cognitive barriers stem from negative stereotypes about women's negotiating abilities. Motivational barriers stem from desire to prevent women negotiators from excelling in a masculine domain. Paradigmatic barriers stem from how negotiation is currently studied. We call for greater attention to motivational barriers and for changes to the negotiation paradigm. Women negotiators are not incompetent, and training them to negotiate more like men is not obviously the solution. In fact, women have greater concern for others than men do, and their cooperativeness elevates collective intelligence and enables ethical behavior. Under a new paradigm of negotiation, the value of these strengths could become more readily apparent. In particular, we advocate for greater attention to long-term relationships, subjective value, and relational capital, all of which may have important economic implications in real world negotiations.